Elementy scjentyzmu światopoglądowego w duchowości Ruchu Raëliańskiego - Kazibut, Radosław (Humaniora. Czasopismo Internetowe, 2026)
Raëlianism is an example of postmodern spirituality, which combines scientism and spirituality, forming an ideological marriage of science and religious beliefs. The Raëlian Movement bases its message on optimism towards scientific and technological progress while criticizing modern science’s epistemological and axiological foundations. Raëlians postulate the need to expand the paradigm of scientific knowledge to include spiritual elements such as telepathy or contact with extraterrestrial beings (Elohim), which leads to the mythologization of science. Their worldview, although inspired by scientism, balances on the borderline of pseudoscience, using paleoastronautics, inteligent design, and genetics as the pillars of “Raëlian science.” This analysis aims to determine whether Raëlianism is a random collection of ideas or a coherent “oxymoron” attempting to reconcile techno-scientific enthusiasm with the spiritual needs of humans in the Anthropocene era.